The endothelial glycocalyx and perioperative lung injury. Issue 1 (February 2017) - Brettner, Florian; von Dossow, Vera; Chappell, Daniel
Abstract : Purpose of review: Ventilator-induced lung injury is a major contributor to perioperative lung injury. The end-expiratory lung volume, regional lung overdistension, and tidal recruitment are known to be the main factors causing subsequent alveolar damage and inflammation. The alveolar-capillary membrane including the endothelial glycocalyx as an integral part of the vascular endothelium seems to play a major role in different kinds of lung injury. Recent findings: Recent studies underline the pivotal importance of the endothelial glycocalyx in lung injury. The glycocalyx regulates and modulates plasma endothelial cell interactions. Several triggers are known to deteriorate the gylcocalyx such as fluid overload, ischemia, and TRALI. The clinical manifestation is inflammation, capillary leak, and edema formation. Breakdown of the endothelial gylcocalyx is of gaining importance in the context of one-lung ventilation, known to be a major risk factor for postoperative lung injury. Studies suggest that volatile anesthetics may have a protective influence on the endothelial glycocalyx of pulmonary capillaries and reduce ischemia-reperfusion injury. This might be of clinical relevance for postoperative outcome. Summary: This review focuses on the involvement of the pulmonary endothelial glycocalyx in the context of perioperative lung injury. The pathophysiological mechanisms and trigger factors of glycocalyx deterioration are discussed, and prevention strategies are taken into consideration.